A VALUABLE FOLK MUSICIAN FROM FUNDU MOLDOVEI – THE SHEPHERD’S PIPE PLAYER LIVIU ŢARAN - DĂNILĂ, Irina Zamfira (Studia Universitatis Babes-Bolyai Musica, 2017)
The present paper presents the the portrait of Liviu Țaran (b. 1961), an important folk musician from Fundu Moldovei village, the county of Suceava, an area of important and rich folk tradition. He is the grandson of a virtuoso shepherd’s pipe player, Ilie Cazacu (1903-1979), who, in turn, was trained by the famous violinist Sidor Andronicescu (1899-1981); both lived in the same village. For almost 70 years, the latter was the conductor of the most famous folk music band in the area. Liviu Țaran learnt how to play the shepherd’s pipe from his grandfather, Ilie Cazacu, whose entire repertoire he took and which he masterfully performs, with a skill which is comparable to his grandfather’s. Liviu Țăran’s repertoire consists of old, genuine folk melodies, dance tunes for certain occasions or casual, “doina” songs, as well as shepherds’ tunes. The virtuoso is a member of an amateurs’ ensemble named “Arcanul”, established in the 70’s in Fundu Moldovei village. The ensemble is still active in performances at home and abroad and promotes genuine folk songs and dance music from Bukovina. To briefly illustrate Liviu Țaran’s repertoire, we added two sample songs in musical notation. Ilie Cazacu’s and Liviu Țaran’s extensive musical activity, as well as their impressive repertoire, are undoubtedly invaluable treasures of the national folklore heritage from Bukovina; they set an example to be followed by the present-day and next generations of performers.